The Role of Religious Leadership In Improving Employee Work Motivation - Yusup; Novianti Andini Putri (Journal of Economy, Accounting and Management Science (JEAMS), 2026)
This study focuses on the role of religious leadership in enhancing employee work motivation at Methy Beauty Clinic. The background of this study is based on the importance of spiritual and moral values in building work ethics and employee enthusiasm in the service sector. The purpose of this study is to analyze the relationship between religious leadership style and employee work motivation levels, and to describe the extent to which the application of religious values influences loyalty and work enthusiasm. The method used is a qualitative approach with observation techniques, in-depth interviews, Focus Group Discussions (FGD), and the distribution of Likert-based questionnaires. The results show that leaders with prominent religious characters based on the values of honesty, sincerity, responsibility, and justice are able to create a harmonious work atmosphere, increase intrinsic motivation, and strengthen employee loyalty. The average score of respondents' perceptions of the variables of religious leadership and work motivation reached 4.68 and 4.58 (strongly agree category). The study confirms that religious leadership plays a significant role in shaping sustainable work motivation, because it combines spiritual aspects and work professionalism, thereby creating a balance between performance, psychological well-being, and spiritual meaning in the organizational environment.